Wobble plate compressor - Sahari, Barkawi (2011)
A wobble plate type compressor for use in gaseous compression systems having a symmetric and multistage configuration is disclosed which includes two sets of different pistons sizes being reciprocated within respective cylinders by two wobble plate members that mirror each other. Multistage configuration will have multi piston diameter sizes that allow for higher gas pressure compression.